(untitled) (Bangladesh Journal of Medical Science, 2022)
Objective: The mandible is the strongest bone in the human skeleton. The uses of the morphological characters of such jawbone is a predominantly used approach in forensic dentistry to determine the gender of a severely damaged cadaver. Distinguishing sex, race and personal stamp of the unknown skeleton still has been the most challenging job in forensic dentistry. This research aimed to clarify the gender of Babylon population by mental foramen (MF) assessment using Orthopantomography (OPG). Method: The present retrospective study was conducted on 120 digital panoramic radiographs. The radiographs were of 60 male and 60 female dentate patients aged between 18-62 years. Morphometric analysis was performed on bilateral mental foramina. Lines were drawn from superior (S) and inferior (I) borders of the foramen and perpendiculars to the lower (L) border of the mandible (S-L and I-L lines respectively). Data were distributed and subjected to statistical analysis using the Independent-Samples T test. Results: The average values of S-L and I-L were significantly higher in males than in females (p<0.05). Conclusion: The distance from the MF to the lower border of the lower jaw reveals gender differences in Babylon city population. Findings also suggest that OPG could be a useful technique for gender identification from the remnants of the human body skeleton. There was a statistical significant difference in the average S-L distance and average I-L distance between males and females at 3 different age groups (young adult, middle age and old age groups), except in the average I-L distance at the middle age group (p<0.05). Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 79-83